Pengaruh Religiusitas Dan Pemanfaatan Online Shop Terhadap Perilaku Konsumtif Mahasiswa Institut Agama Islam Tafaqquh Fiddin Dumai - Khairul Azmi; Fikri Walhadi; Robiyatul Adawiyah (Lembaga Bale Literasi, 2026)
The development of digital technology encourages student consumer behavior, so the role of religiosity is needed in directing selective and sharia-compliant consumption. This study aims to determine the influence of religiosity and the use of online shops on the consumer behavior of students at the Tafaqquh Fiddin Islamic Institute, Dumai. The research method used is a quantitative method. The data used in this study are primary data obtained through distributing questionnaires to students. The population in this study was 402 students. Sampling was carried out using Ari Kunto's theory so that the number was 100 students. This study used a Simple Random Sampling technique. Data were analyzed using multiple linear regression analysis, with the help of SPSS 21.0 software for Windows. The results of the study indicate that religiosity and the use of online shops simultaneously have a positive and significant effect on the consumer behavior of students at the Tafaqquh Fiddin Islamic Institute, Dumai. With an influence of 74% and the remaining 26% is influenced by other factors